Toward T Cell-Mediated Control or Elimination of HIV Reservoirs: Lessons From Cancer Immunology - Mylvaganam, Geetha; Yanez, Adrienne G.; Maus, Marcela; Walker, Bruce D. (Frontiers in Immunology, 2019)
As the AIDS epidemic unfolded, the appearance of opportunistic infections in at-risk persons provided clues to the underlying problem: a dramatic defect in cell-mediated immunity associated with infection and depletion of CD4+ T lymphocytes. Moreover, the emergence of HIV-associated malignancies in these same individuals was a clear indication of the significant role effective cellular immunity plays in combating cancers. As research in the HIV field progressed, advances included the first demonstration of the role of PD-1 in human T cell exhaustion, and the development of gene-modified T cell therapies, including chimeric antigen receptor (CAR) T cells. In the intervening years, the oncology field has capitalized on these advances, effectively mobilizing the cellular immune response to achieve immune-mediated remission or cure of previously intractable cancers. Although similar therapeutic advances have not yet been achieved in the HIV field, spontaneous CD8+ T cell mediated remission or functional cure of HIV infection does occur in very small subset of individuals in the absence of anti-retroviral therapy (ART). This has many similarities to the CD8+ T cell mediated functional control or elimination of cancers, and indicates that immunotherapy for HIV is a rational goal. In HIV infection, one major barrier to successful immunotherapy is the small, persistent population of infected CD4+ T cells, the viral reservoir, which evades pharmacological and immune-mediated clearance, and is largely maintained in secondary lymphoid tissues at sites where CD8+ T cells have limited access and/or function. The reservoir-enriched lymphoid microenvironment bears a striking resemblance to the tumor microenvironment of many solid tumors–namely high levels of anti-inflammatory cytokines, expression of co-inhibitory receptors and physical exclusion of immune effector cells. Here we review the parallels between CD8+ T cell-mediated immune control of HIV and cancer, and how advances in cancer immunotherapy may provide insights to direct the development of effective HIV cure strategies. Specifically, understanding the impact of the tissue microenvironment on T cell function and development of CAR T cells and therapeutic vaccines deserve robust attention on the path toward a CD8+ T cell mediated cure of HIV infection.